La modélisation graphique de phénomènes émergents pour répondre aux besoins de la prospective - Laure Casanova Enault (OpenEdition, 2017)
The graphic modeling of prospective scenarios developed under the Sustainable Territory 2030 program – developed by the Ministry of Ecology, Sustainable Development and Energy – oﬀered an opportunity to examine the adjustment of the method to the needs of prospective representation. The challenge was to experiment new ways to represent two topics that are diﬃcult to grasp with the method; but which have become decisive in the understanding of territorial evolution due to the generalization of the reference base for sustainable development: the environment and governance.